Microformats in software agent development - Stanek, Stanisław; Żytniewski, Mariusz (Zastosowanie mikroformatów w budowie agentów programowych, 2012)
The article is focused on issues concerning the development of the semantic Web and the possibility of using microformats in software agent technologies. The first section provides an introduction to the information society and Web 2.0. The second section outlines the concepts of the semantic Web and microformats, and presents a sample application of the JENA library. The final section delivers conclusions
Informatyka Ekonomiczna = Business Informatics, 2012, Nr 2 (24), s. 82-90
Keywords: semantic Internet; microformats; software agent